Analisis Vegetasi Tumbuhan Bawah Metode Garis Menyinggung Dan Titik Menyinggung Di Hutan Kampus IPB Dramaga - Taufik Arianto; Firman Ali Rahman; Masyarani Sulaiman; Yuliantin; Sulistijorini (Bioindikator: Jurnal Biologi dan Pendidikan Biologi, 2024)
The diversity of vegetation can reflect the vegetation structure of an area against information on species composition, distribution patterns, density patterns, frequencies, and species dominance to determine the important value index of the forest community composition of a plant species. This study aims to analyze understory vegetation in the IPB Dramaga Campus Forest using two main methods, namely line intercept and point intercept. Both methods are applied to compare the effectiveness of measuring ecological parameters such as density, frequency, dominance, and understory diversity index. The results showed that there were 10 types of plants with the line intercept method including Digitaria fuscencens, Spilanthes paniculata, Cleome vicicosa, Clitorea Ternatea, Digitaria longifora, Britaria reptans, Ageraitum conzoides, Imperacta clindraca, Hevea braziliensis, Paku. Meanwhile, in the tangent point method, 5 species were found at the research method line points as follows: Digitaria fuscencens, Spilanthes paniculata, Clitorea Ternatea, Digitaria longifora, Altherenthera philoxeoriides. The analysis of the importance value index in the tangent line method showed that Spilanthes paniculata dominated the understory vegetation with an importance value index of 145.91%, followed by Digitaria fuscencens (48.39%) and Digitaria longifora (40.58%). Meanwhile, in the tangent point method, Digitaria fuscencens had the highest importance value index of 69.46%, followed by Spilanthes paniculata (69.20%) and Clitorea ternatea (40.65%), with the lowest importance value index of Digitaria longifora (16.52%) and Altherenthera philoxeoriides (7.17%). The tangent line method is more effective in describing the horizontal distribution of vegetation, while the tangent point method provides high precision in estimating relative cover. The understory vegetation in this area is dominated by certain species that have high adaptation to the IPB University campus forest environment.